Категория пародии и трагизма в романе Татьяны Толстой „Кысь” - Chudzińska-Parkosadze, Anna (Studia Rossica Posnaniensia, 2015)
This article presents an attempt to specify the categories of parody and tragedy in the novel The Slynx which was written by Tatyana Tolstaya. Since the novel is a postmodern work, the presence of parody seems to be obvious. However, the category of tragedy in a work of this type is a curious novelty, which is analyzed by the author of this article.